2016
DOI: 10.1109/tits.2016.2521779
|View full text |Cite
|
Sign up to set email alerts
|

Solving the Dynamic Vehicle Routing Problem Under Traffic Congestion

Abstract: This paper proposes a dynamic vehicle routing problem (DVRP) model with nonstationary stochastic travel times under traffic congestion. Depending on the traffic conditions, the travel time between two nodes, particularly in a city, may not be proportional to distance and changes both dynamically and stochastically over time. Considering this environment, we propose a Markov decision process model to solve this problem and adopt a rollout-based approach to the solution, using approximate dynamic programming to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(37 citation statements)
references
References 42 publications
0
37
0
Order By: Relevance
“…Firstly, all possible travel paths were represented by three n * n matrices. Next, the time, speed, distance, fuel consumption and cost values of the different labeled paths A, B and C, respectively, were plugged into the above matrix, where the values of distance and time were derived from the traffic information management system, the fuel consumption was calculated by Equations (5) and (6) and the cost values were calculated by Equations (7)- (10). The driving speed on the arc (i, j) was s ij = d ij /t ij ; the specific matrix data are shown in the Appendix A, Table A1.…”
Section: The Adjacency-matrix Representation Of a Multi-pathmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, all possible travel paths were represented by three n * n matrices. Next, the time, speed, distance, fuel consumption and cost values of the different labeled paths A, B and C, respectively, were plugged into the above matrix, where the values of distance and time were derived from the traffic information management system, the fuel consumption was calculated by Equations (5) and (6) and the cost values were calculated by Equations (7)- (10). The driving speed on the arc (i, j) was s ij = d ij /t ij ; the specific matrix data are shown in the Appendix A, Table A1.…”
Section: The Adjacency-matrix Representation Of a Multi-pathmentioning
confidence: 99%
“…This method has been widely used in other studies. Kim et al [10] used a heuristic algorithm to solve the time-dependent vehicle routing problem (TDVRP) in dynamic vehicle routing problems and reported that using the time-dependent shortest path in TDVRP can significantly reduce vehicle travel time. Bektas and Laporte [11] analyzed the pollution routing problem based on emission and energy consumption models; moreover, the effects of time windows, speed, distance and other factors on vehicle emissions were considered.…”
Section: Introductionmentioning
confidence: 99%
“…In our approach, we adopted two crossover strategies. The first is that the Best-Cost Route Crossover (BCRC) employed in [12,20]. The second is the closest distance and maximum saving route crossover with priority to satisfy the capacity constraint (CMRCSC).…”
Section: Crossovermentioning
confidence: 99%
“…Perhaps the closest to ours CVRP formulation is presented in [21] where both stochastic travel times a.nd online adaptation of the solution by means of 140 Monte Carlo (MC) simulations is proposed. On a less general note, however, both papers differ in the following major aspects.…”
mentioning
confidence: 99%
“…On a less general note, however, both papers differ in the following major aspects. Firstly, in [21] the problem is decomposed into independent single-vehicle problems contrary to global optimization performed in this paper. Secondly, the experiments in [21] are based on an in-house real-time traffic data ( owned by logistic company from Singapore) and not on publicly available benchmarks.…”
mentioning
confidence: 99%